Legumain is upregulated in acute cardiovascular events and associated with improved outcome - potentially related to anti-inflammatory effects on macrophages. (March 2020) - Lunde, Ngoc Nguyen; Gregersen, Ida; Ueland, Thor; Shetelig, Christian; Holm, Sverre; Kong, Xiang Yi; Michelsen, Annika E.; Otterdal, Kari; Yndestad, Arne; Broch, Kaspar; Gullestad, Lars; Nyman, Tuula A.; et al.
Abstract: Background and aims: We have previously found increased levels of the cysteine protease legumain in plasma and plaques from patients with carotid atherosclerosis. This study further investigated legumain during acute cardiovascular events. Methods: Circulating levels of legumain from patients and legumain released from platelets were assessed by enzyme-linked-immunosorbent assay. Quantitative PCR and immunoblotting were used to study expression, while localization was visualized by immunohistochemistry. Results: In the SUMMIT Malmö cohort (n = 339 with or without type 2 diabetes and/or cardiovascular disease [CVD], and 64 healthy controls), the levels of circulating legumain were associated with the presence of CVD in non-diabetics, with no relation to outcome. In symptomatic carotid plaques and in samples from both coronary and intracerebral thrombi obtained during acute cardiovascular events, legumain was co-localized with macrophages in the same regions as platelets. In vitro, legumain was shown to be present in and released from platelets upon activation. In addition, THP-1 macrophages exposed to releasate from activated platelets showed increased legumain expression. Interestingly, primary peripheral blood mononuclear cells stimulated with recombinant legumain promoted anti-inflammatory responses. Finally, in a STEMI population ( POSTEMI ; n = 272), patients had significantly higher circulating legumain before and immediately after percutaneous coronary intervention compared with healthy controls (n = 67), and high levels were associated with improved outcome. Conclusions: Our data demonstrate for the first time that legumain is upregulated during acute cardiovascular events and is associated with improved outcome. Graphical abstract: Image 1 Highlights: High circulating levels of legumain in patients with stable or acute cardiovascular disease. High circulating legumain in the acute phase is correlated with improved outcome. Platelets contain, release and could be sources of circulating legumain. Extracellular legumain mediates anti-inflammatory responses in primary monocytes.